1989
DOI: 10.1164/ajrccm/140.4.958
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin D Activity Is Increased in Alveolar Macrophages and Bronchoalveolar Lavage Fluid of Smokers

Abstract: Cathepsin D activity was determined in alveolar macrophages (AM) and cell-free bronchoalveolar lavage fluid (BALF) from volunteers who were current cigarette smokers and compared with that found in lifetime nonsmokers. Enzyme activity was determined with a highly sensitive and specific substrate [D-Phe-Ser(0-CH2-C6H5)-Phe-Phe-Ala-Ala-pAB]. Specific activity was more than three times higher in AM from smokers than in cells from nonsmokers (37,880 +/- 2,090 versus 10,300 +/- 1,200; p less than 0.001) and approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 7 publications
4
20
0
2
Order By: Relevance
“…This is the first evidence indicating association of Cath H expression or regulation with cigarette smoking in human lung cancer and is consistent with previous studies revealing an increase of Cath B and L activity in lung tissue of smokers (Knoch et al, 1994;Werle et al, 1995), in their alveolar macrophages and alveolar lavage fluid (Chang et al, 1986;Takahashi et al, 1993) as well as in alveolar macrophages and bronchoalveolar lavage fluid of rats exposed to cigarette smoke Lesser et al, 1989;Chapman et al, 1997). Furthermore, Yukio Ishii (1991aIshii ( , 1991b clearly demonstrated that Cath H is secreted mainly with surfactant from Type II alveolar epithelial cells and alveolar macrophages of rat lung.…”
Section: Discussionsupporting
confidence: 92%
“…This is the first evidence indicating association of Cath H expression or regulation with cigarette smoking in human lung cancer and is consistent with previous studies revealing an increase of Cath B and L activity in lung tissue of smokers (Knoch et al, 1994;Werle et al, 1995), in their alveolar macrophages and alveolar lavage fluid (Chang et al, 1986;Takahashi et al, 1993) as well as in alveolar macrophages and bronchoalveolar lavage fluid of rats exposed to cigarette smoke Lesser et al, 1989;Chapman et al, 1997). Furthermore, Yukio Ishii (1991aIshii ( , 1991b clearly demonstrated that Cath H is secreted mainly with surfactant from Type II alveolar epithelial cells and alveolar macrophages of rat lung.…”
Section: Discussionsupporting
confidence: 92%
“…Lysosomal proteinases intracellularly complete the extracellular cleavage of collagens, elastin and proteoglycan core proteins by serine and metalloproteinases [7]. They are partially secreted into the extracellular space and the bronchoalveolar lavage fluid (BALF) [6,7,14,15]. The activities of cysteine proteinases are controlled by their endogenous inhibitors, the cystatins [6,7,16].…”
mentioning
confidence: 99%
“…This aspartyl endoprotease is closely associated with tumour progression in some human malignancies including Lung cytotoxicity of combined exposure to refractory ceramic fibres and cigarette smoke 384 lung adenocarcinoma 29 , it is overexpressed in inflammatory status 30 and modulated by inflammatory mediators. Cigarette smoke was described as a potent inducer of this enzyme activity in AM 31 . Examination of the effect of RCF cigarette smoke on cells in lung tissue results into the following conclusions: (i) The expected cytotoxicity of RCF was confirmed by the significant decrease in viability of AM, significant increase in CATD activity in cfBALF, and significant increase in ACP and CATD activity in BALF cells; (ii) Cytotoxic activity of cigarette smoke was demonstrated by the significant decrease in viability of AM, significant decrease in phagocytic activity of AM, significant increase of ACP and CATD activity in cfBALF, and significant increase of ACP and CATD activity in BALF cells.…”
Section: Figmentioning
confidence: 99%